Pengaruh Kualitas Audit Terhadap Manajemen Laba pada Perusahaan Perbankan yang Terdaftar di BEI Tahun 2013-2016 - Asri Mustika, Ni Wayan; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 25 No 1 (2018)DO - 10.24843/EJA.2018.v25.i01.p17, 2018)
Earnings management practices have occurred with Enron Corp. Profit management is defined as the difference between the realized revenues from transactions occurring during one period and the costs associated with the income. The purpose of this study is to examine the effect of audit quality on earnings management. The audit quality in this study is measured by the size of the Public Accounting Firm (KAP), the auditor of industry specialization, and the independence of auditors. This study uses secondary data of financial statements of banking companies listed on the Indonesia Stock Exchange in 2013-2016. This study uses purposive sampling, with 64 samples of banking companies. Data analysis method used in this research is multiple linear regression test. The results showed that the size of KAP does not affect the earnings management. Meanwhile, industry specialist auditor and auditor independence have an effect on earnings management. Keywords: Audit quality, KAP measures, industry specialization auditors.